2021
DOI: 10.1007/s10639-021-10796-6
|View full text |Cite
|
Sign up to set email alerts
|

When color coding backfires: A guidance reversal effect when learning with realistic visualizations

Abstract: Digital learning increasingly makes use of realistic visualizations, although realism can be demanding for learners. Color coding is a popular way of helping learners understand visualizations and has been found to aid in learning with detailed visualizations. However, previous research has shown that color coding must not always be an effective aid, and that it even may reduce retention when used with simple visualizations. This study assessed whether the presence of color coding in learning tests has an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Many genetics lessons use visual representations, such as media (Solomon & Johnson, 2000), manipulatives (Venville & Donovan, 2007), or diagrams, such as pedigree diagrams (Mathiaparanam et al, 2022). Visual representations have been found to promote learning of science concepts (Mayer, 2009;Mayer & Moreno, 2003;Schnotz, 2002); however their effectiveness depends on many factors, including their perceptual features (Rey, 2012;Skulmowski, 2022aSkulmowski, , 2022b. Perceptually rich visualizations (e.g., realistic images) often help students learn the information presented in the lesson, but might not help them generalize to other material (Rey, 2012;Skulmowski, 2023).…”
Section: The Role Of Instruction In Genetics Learningmentioning
confidence: 99%
“…Many genetics lessons use visual representations, such as media (Solomon & Johnson, 2000), manipulatives (Venville & Donovan, 2007), or diagrams, such as pedigree diagrams (Mathiaparanam et al, 2022). Visual representations have been found to promote learning of science concepts (Mayer, 2009;Mayer & Moreno, 2003;Schnotz, 2002); however their effectiveness depends on many factors, including their perceptual features (Rey, 2012;Skulmowski, 2022aSkulmowski, , 2022b. Perceptually rich visualizations (e.g., realistic images) often help students learn the information presented in the lesson, but might not help them generalize to other material (Rey, 2012;Skulmowski, 2023).…”
Section: The Role Of Instruction In Genetics Learningmentioning
confidence: 99%
“…However, in presentations of renderings that do not feature rotatable 3D models, spatial ability has not been found to be a significant influence on learning (Huk et al 2010 ). As the 3D models used in the visualizations of the two present experiments were not rotatable by the participants (see Skulmowski 2022b ) and are rather flat in their design (as most of the visualizations show cross sections), it is unlikely that spatial ability could have had a major impact in the studies. Furthermore, the sample sizes of the studies are large enough to assume that the spatial ability of the participants was sufficiently balanced in order to avoid a confounding influence of spatial ability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study on anatomy learning found that learning with realistic visualizations mainly has positive effects if the learning test makes use of the experience with the realistic representation, such as if the images used in a learning tests were also prepared in a realistic style (Skulmowski and Rey 2021 ). Moreover, two studies have revealed that higher levels of realism can result in better retention performance (or better performance for parts of a visualization that were rendered realistically), but at the same time increase subjective cognitive load (Skulmowski 2022a , b ; Skulmowski and Rey 2020 ). However, the desire to explore objects has been found to increase with higher levels of perceived realism (Höst et al 2022 ), providing another potential advantage of realistic visuals for learning.…”
Section: Introductionmentioning
confidence: 99%